Dukungan Sosial Keluarga dan Kesehatan Mental pada Warga Binaan Pemasyarakatan - Deni Yusup Prasetio; Arni Nur Rahmawati; Maya Safitri (JURNAL KEPERAWATAN MERSI, 2025)
Background: Prison inmates are vulnerable to mental health disorders due to psychological stress during their sentence. Family social support is believed to play a protective role in maintaining psychological stability. Objective: The purpose of this study was to determine the relationship between family social support and mental health among inmates at the Class IIB Banyumas State Detention Center. Methods: The research method used a quantitative design with a cross-sectional approach. The sample size was 185 respondents using a total sampling technique. The research instruments included a family social support questionnaire (14 items) and the SRQ-20 (20 items) to assess mental health. Data analysis was performed using the Chi-Square test. Results: The results showed that the majority of respondents reported moderate (45.9%) to high (37.8%) family social support. Most respondents did not experience symptoms of mental disorders (84.9%), while the remainder experienced mild (12.4%), moderate (2.2%), and severe (0.5%) symptoms. Statistical tests showed a significant relationship between family social support and mental health (p=0.008). Conclusion: Family social support is significantly associated with the mental health of inmates. The higher the level of family support received, the better the mental health of inmates.